2018
DOI: 10.1590/2317-6431-2018-2032
|View full text |Cite
|
Sign up to set email alerts
|

Evidências científicas da reabilitação vestibular na atenção primária à saúde: uma revisão sistemática

Abstract: Purpose: Investigate in the literature the effectiveness of treatments used for vestibular rehabilitation (VR) in PHC. Research strategy: The search of publications on VR in PHC was carried out in electronic databases MEDLINE (access by PubMed), PEDro and Web of Science. Selection criteria: Controlled clinical trials were selected in English, Spanish and Portuguese. The methodological quality of the studies was evaluated using the PEDro scale. The analysis of the results was examined through a critical review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 11 publications
2
15
0
11
Order By: Relevance
“…However, the negative implications of this limitation for the main outcomes were softened due to the presence of the traditional VR group, which have their effects known and established in the literature. 8,[14][15][16][17][18] The present study showed changes in the flow of care for patients with dizziness complaints treated in the areas covered by the basic health units examined, increasing the possibility of expanding this discussion to other health units in Belo Horizonte and nationally, throughout the SUS. Future studies that expand the findings to the national public health system are warranted.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…However, the negative implications of this limitation for the main outcomes were softened due to the presence of the traditional VR group, which have their effects known and established in the literature. 8,[14][15][16][17][18] The present study showed changes in the flow of care for patients with dizziness complaints treated in the areas covered by the basic health units examined, increasing the possibility of expanding this discussion to other health units in Belo Horizonte and nationally, throughout the SUS. Future studies that expand the findings to the national public health system are warranted.…”
Section: Discussionmentioning
confidence: 97%
“…The objective of the present study was to evaluate the effectiveness of two treatment methods for PHC patients with dizziness: VR, a conventional method with proven benefits that is considered to be an effective therapeutic treatment in PHC, 8,9,[13][14][15][16][17][18] and LG, an alternative method. The practice of LG has been reported in the literature to offer health benefits.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations